2021
DOI: 10.3390/microorganisms9040802
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Unique Cold-Active Lipases Derived from a Novel Deep-Sea Cold Seep Bacterium

Abstract: The deep ocean microbiota has unexplored potential to provide enzymes with unique characteristics. In order to obtain cold-active lipases, bacterial strains isolated from the sediment of the deep-sea cold seep were screened, and a novel strain gcc21 exhibited a high lipase catalytic activity, even at the low temperature of 4 °C. The strain gcc21 was identified and proposed to represent a new species of Pseudomonas according to its physiological, biochemical, and genomic characteristics; it was named Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Other factors responsible for the flexibility of such enzymes include enhanced surface, core hydrophobicity and the arrangement of aminoacids. Some of the latest reports strongly support that the presence and orientation of specific amino acids within the structure of enzyme affects the stability and activity, for example, the catalytic triads Ser, His and Asp in lipase encoding genes found in P. marinensis were observed to be necessary for preserving enzyme functions ( Guo et al, 2021 ). Öten et al (2022) observed a boost in the adaptation of enzymes to cold conditions by proline (Pro) and glycine (Gly) residues modifying conformational changes in the three-dimensional (3-D) structure of proteins.…”
Section: Adaptation Strategies – a Facet Of Versatilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors responsible for the flexibility of such enzymes include enhanced surface, core hydrophobicity and the arrangement of aminoacids. Some of the latest reports strongly support that the presence and orientation of specific amino acids within the structure of enzyme affects the stability and activity, for example, the catalytic triads Ser, His and Asp in lipase encoding genes found in P. marinensis were observed to be necessary for preserving enzyme functions ( Guo et al, 2021 ). Öten et al (2022) observed a boost in the adaptation of enzymes to cold conditions by proline (Pro) and glycine (Gly) residues modifying conformational changes in the three-dimensional (3-D) structure of proteins.…”
Section: Adaptation Strategies – a Facet Of Versatilitymentioning
confidence: 99%
“… Zhang and Zeng (2011) reported the identification of the amylase gene from the psychrotolerant P. stutzeri strain 7,193. Numerous other Pseudomonas species isolated from the regions like Indian Himalaya ( Salwan et al, 2010 ; Jain and Pandey, 2016 ; Pandey et al, 2019 ; Jain et al, 2020 ), Ny-Alesund, Svalbard, Arctic ( Srinivas et al, 2009 ), Humboldt Glacier, Mount Humboldt, Andean region of Venezuela ( Ball et al, 2014 ) have been studied for production of industrially important enzymes such as amylases, proteases, RNA polymerase and lipases ( Uma et al, 1999 ; Zhang and Zeng, 2011 ; Jain et al, 2017 ; Salwoom et al, 2019 ; Guo et al, 2021 ). Beside mountains, the oceans represent an untapped potential that exists in the microbiome to produce enzymes with distinctive properties.…”
Section: Industrial Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of this bacterial genus for several industrial applications was revealed. Guo et al [3] isolated bacterial strains from the sediment of deep-sea cold seep, finding a novel strain that exhibited high cold-active (4 • C) lipase activity. This strain was proposed to constitute a new species of Pseudomonas, and was named P. marinensis.…”
mentioning
confidence: 99%